ANALYZING FINANCIAL PERFORMANCE: HOW FINANCIAL RATIOS INFLUENCE THE STOCK PRICE OF PT BANK CENTRAL ASIA - Angellita Pereira, Patricia; Kusumahadi, Teresia Angelia (Universitas Muhammadiyah Kalimantan Timur, 2024)
This study aims to investigate the impact of financial performance indicators and the COVID-19 pandemic on the stock price of PT Bank Central Asia Tbk. Utilizing a quantitative approach, the research analyzes data from 2016 to 2023, focusing on key financial indicators such as capital adequacy ratio, net interest margin, non-performing loans, and loan-to-deposit ratio. The analysis employs statistical tests to determine the relationships between these financial indicators and the bank’s stock price. The findings reveal that the capital adequacy ratio and loan-to-deposit ratio positively influence the stock price in the long term, while net interest margin and non-performing loans do not show a significant effect. Additionally, the COVID-19 pandemic did not lead to substantial fluctuations in stock price, suggesting that the bank's strong financial fundamentals provided resilience during the crisis. These results underscore the importance of maintaining robust capital reserves and effective liquidity management to enhance investor confidence and ensure sustainable growth in the banking sector. The study offers valuable insights for investors and policymakers, highlighting the need for prudent financial practices in navigating economic uncertainties.